Editors' Introduction: Authority, Legitimacy, and Vulnerability in Contemporary Asia - Asep Muhamad Iqbal (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2025)
Abstract This JASSR Vol. 7, No. 2 (2025) frames the intertwined questions of authority, legitimacy, and vulnerability in contemporary Asia. Drawing on Weber and Suchman, it argues that legitimacy is produced, contested, and repaired in everyday arenas such as digital religious communication, sacred memory, marriage and gender relations, regional policy, welfare distribution, and apology diplomacy. The issue brings together studies on Pakistani imams’ perceptions of online extremism, Islamic iconization in Madura, divorced women’s experiences in Bangladesh, Indonesia’s support for ASEAN gender mainstreaming, Bangladesh’s Open Market Sale programme, and apology diplomacy in Philippine tourism. Together, the articles show how Asian social science can illuminate the lived processes through which institutions, communities, and individuals negotiate trust, care, recognition, and public authority.